Proposal of new specific status for tea-infesting populations of the nominal citrus spiny whitefly Aleurocanthus spiniferus (Homoptera: Aleyrodidae) - Kanmiya, Kenkichi; Ueda, Shigenori; Kasai, Atsushi; Yamashita, Koji; Sato, Yasushi; Yoshiyasu, Yutaka (Zootaxa, 2011)
The citrus spiny whitefly Aleurocanthus spiniferus (Quaintance) is a pest of citrus plants that is native to South-East Asia. Although serious outbreaks of the tea-infesting whitefly in China, Taiwan and Japan have been attributed to this species over the last 20 years, recent research has shown different host preferences between the two whiteflies. Hence, the two pests have tentatively been differentiated as tea-infesting and citrus-infesting populations. We further compared morphological, acoustic and genomic features between the two populations in Japan. Morphological differences were recognised in the arrangement of spines, porettes and papillae on the dorsal disc and number of marginal crenulations and marginal waxy fringe of 4 th -instar nymphs, as well as wing maculation and genitalic organs of adults. In courtship behaviour, the acoustic properties of male vibratory signals also differed between the two. Furthermore, genetic analysis of mtCOI sequences (759 bp) showed that the tea-infesting population was clearly distinct from the citrus-infesting group, with high bootstrap values. The mtCOI sequence identities were 76.2% between the two populations. Genetic differentiation between the two populations was shown by the high value (0.99650) of pairwise Fst, indicating the sexual isolation of the two populations. Consequently, these two populations are regarded as different representatives, consisting of a sibling relationship, but clearly distinguished from each other as independent genomic populations. Here, we describe the tea-infesting population and propose a new scientific name, Aleurocanthus camelliae Kanmiya & Kasai sp. nov., and a new common name, camellia spiny whitefly, thus distinguishing it from A. spiniferus (Quaintance), the citrus spiny whitefly that constitutes the citrus-infesting population.